A Cognitive Linguistic Study of the Satirical Language in Al-Hajjar's Caricatures (Journal of the College of Education for Women, 2019)
The present study is a qualitative study that aims to investigate the way the Iraqi caricaturist,Dheaa Al-Hajjar uses caricatures to produce a satirical meaning humorously.Producing satire while at the same maintaining humor requires a creative thinking on the part of the caricaturist. Thus, the study examines the production of humorous satire in terms of creativity. The analysis is done from the cognitive linguistic point of view using Arthur Koestler's theory of bisociation as presented in his book The Act of Creation in 1964. The main principle on which the theory is based is that humor is created via linking (or bisociating in Koestler's terms) two habitually incompatible trains of thought in order to come up with a novel meaning that is both logical and unexpected. This novel meaning is the focal point, which Koestler calls the Eureka point, where the incompatibility is resolved. The study is again cognitive as it confirms the cognitive linguistic principle, which reads that language is thought.The study concludes that Al-Hajjar manipulated different figurative types like metaphor, symbolism, etc. as well as humor types like irony and sarcasm in the production of satire benefitting from the incompatibility that occurs in the creative production of satire. It further reveals that irony dominated most of his studied caricatures.